Жуки-горбатки (Coleoptera, Mordellidae) фауны Казахстана и Средней Азии. Сообщение 2 - Односум, В.К. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Приведена оригинальная определительная таблица жуков-горбаток рода Mordellistena Costa фауны Казахстана и Средней Азии по самцам с привлечением нового ключевого видового диагностического признака — формы пигидия и его пропорций к диску переднегруди, а также новые данные по их морфологической изменчивости и распространению. Описаны Mordellistena turkmenica Odnosum, sp. n. из Туркменистана и M. kirghizica Odnosum, sp. n. из Кыргызстана. Типовой материал новых видов хранятся в Институте зоологии им. И. И. Шмальгаузена (Киев). A key to males of mordellid species of the genus Mordellistena Costa occurring in Kazakhstan and Middle Asia, with addition of newly discovered characters (e. g., shape of the pygidium and its ratios comparing to the anal sternite, elytra and prothoracal disc), new data on morphological variability and distribution are provided. Mordellistena turkmenica Odnosum, sp. n. (type locality: Turkmenia, Kara-Kala distr., Kopet-Dag, Nokhur vill.) and M. kirghizica Odnosum, sp. n. (type locality: Kirghizia, vicinity of Przewalsk, Kara-Kol Ravine) are described. Types are deposited at the Schmalhausen Institute of Zoology (Kyiv).